Madrasah Principal Leadership in Increasing Work Motivation Teachers at Madrasah Tsanawiyah Negeri Batang Hari - Romadhon, Romadhon; Badarussyamsi, Badarussyamsi; Fadhil, M. (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This study aims to analyze and describe (1) How is the work motivation of teachers at Madrasah Tsanawiyah Negeri 1 Batang Hari (2) How does the Principal carry out his role as a motivator at Madrasah Tsanawiyah Negeri 1 Batang Hari (3) How is the Principal's effort in improving teacher performance at Madrasah Tsanawiyah Negeri 1 Batang Hari. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation. The main informants in this study were the principal, teachers, and administrative staff. The results of this study are (1) The Principal of Madrasah in providing work motivation to teachers by encouraging teachers to attend relevant seminars or workshops. The Principal accepts suggestions and criticisms that arise from all parties, be it teachers, staff, and other employees. Conducts ongoing supervision and conducts evaluations (2) The Principal of Madrasah as a motivator by fostering a sense of togetherness, solidarity, and good cooperation towards teachers with a sense of family. Builds a positive and collaborative organizational climate. (3) The efforts of the Head of Madrasah to improve performance by providing teacher performance coaching, supervising teacher performance, providing motivation to teachers and creating a conducive working atmosphere and implementing madrasah rules with discipline